2013
DOI: 10.1128/aac.01430-12
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacodynamics of Anidulafungin against Clinical Aspergillus fumigatus Isolates in a Nonneutropenic Murine Model of Disseminated Aspergillosis

Abstract: A spergillus fumigatus may cause life-threatening infections in both immunocompetent and immunocompromised patients (1-3). Voriconazole (VCZ) is considered the first choice of therapy for invasive aspergillosis (IA) (4, 5). However, the rate of azole resistance is increasing in A. fumigatus, which significantly complicates the management of IA, as azole resistance is associated with therapeutic failure and a mortality rate of up to 88% (6-13). Primary invasive infections due to resistant isolates involving the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 30 publications
1
17
0
1
Order By: Relevance
“…The efficacy of voriconazole monotherapy was determined in an immunocompetent mouse model of disseminated aspergillosis following intravenous inoculation, as described previously (18,(32)(33)(34). Animals were infected via injection into the lateral tail of the mouse of 0.1 ml of the conidial suspension corresponding to the LD 90 for each isolate.…”
Section: Fungal Isolates Four Clinicalmentioning
confidence: 99%
“…The efficacy of voriconazole monotherapy was determined in an immunocompetent mouse model of disseminated aspergillosis following intravenous inoculation, as described previously (18,(32)(33)(34). Animals were infected via injection into the lateral tail of the mouse of 0.1 ml of the conidial suspension corresponding to the LD 90 for each isolate.…”
Section: Fungal Isolates Four Clinicalmentioning
confidence: 99%
“…However, the same study showed that although therapy success increased with increasing dosages of the drug, the maximum response was not obtained, even at 20 mg/kg. Furthermore, increasing the dose to 40 mg/kg caused toxic side effects (41). In our study, we did not increase the anidulafungin concentration but slightly reduced the fungal load by maintaining 100% mortality in the control group.…”
Section: Discussionmentioning
confidence: 66%
“…Under therapy with anidulafungin at 10 mg/kg/day, only 18% of animals survived (40). A recent analysis of the pharmacokinetics of anidulafungin in mice revealed a good correlation of serum level with the applied dose, which indicates that an effective concentration in serum can be achieved (41). However, the same study showed that although therapy success increased with increasing dosages of the drug, the maximum response was not obtained, even at 20 mg/kg.…”
Section: Discussionmentioning
confidence: 75%
“…A total of 604 outbred CD-1 (Charles River, the Netherlands) female mice, 4 to 5 weeks old, weighing 20 to 25 g, were randomized into groups of 11 mice for L-AmB monotherapy. Animals were infected using the procedure described before (11,13,15,25). Before performing the experiment, the isolates were cultured once on SAD for 5 days at 35 to 37°C and subcultured twice on 15-cm Takashio slants for 5 days at 35 to 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, it is important to explore alternative treatment regimens. Lipid formulations of the amphotericin B and echinocandin antifungals or combination therapy may be important alternative options, in patients with azole-resistant Aspergillus diseases.We previously investigated the pharmacodynamics of anidulafungin monotherapy and the combination of voriconazole and anidulafungin (13)(14)(15). Although anidulafungin treatment improved the survival of mice in a dose-dependent manner, a maximal response was not achieved when mice were infected with an azole-susceptible or azole-resistant isolate, even in those treated with the highest anidulafungin dose.…”
mentioning
confidence: 99%